Friends personalization of trustworthiness for privacy perseverance in social networking - Singh, M.M. (Newswood Limited, 2015)
Online Social Network (OSN) has become the most popular platform on the Internet that can provide an interesting and creative ways to communicate, sharing and meets with peoples. Trust concerns have been raised and the trustworthiness of social networking sites has been questioned. Currently, the trust in social networks is using the single- faceted approach, which is not well personalized, and doesn't account for the subjective views of trust according to each user, but only the general trust believes of a group of population. From our initial survey, we had found that most people can share their information without any doubts on OSN but they normally do not trust all their friends equally and think there is a need of trust management. By adopting the idea of multi-faceted trust model, a user-centric model that can personalize the comments/photos in social network with user's customized traits of trust is proposed. In this paper, the initial result is analyzed in determining the need to enhance the current trust model within the current social networking.